Kako celoviteje prepoznavati, preprečevati in obvladovati probleme - Rosi, Bojan (Organizacija (Kranj), 2006)
We humans regularly face problems, conflicts, and crises. Are we able to recognize them in time and requisitely holistically to comprehend, prevent, or solve them, at least? Often we do try to solve problems / problematiques, conflicts, and crises in an efficient and effective, hence systemic way. Unfortunately, we find again and again, that in our behavior, action, life practice, we are too narrow-minded, one-sided, remaining on the level of a single specialized expertise and profession only. Therefore we lack interdisciplinary, co-operative and creative approaches; innovation lacks. Briefly, we often find that we are not meeting the law of requisite holism. This makes us unable to solve our "difficulties" in a satisfactory and long-term style. Dialectical network thinking is a new methodology able to help us in such efforts.
Keywords: management; podjetja; problemi; konflikti; krize; reševanje problemov; reševanje konfliktov; strategija